(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: The research aimed to investigate the impact of reducing blood uric acid and the toxicity of dried lolot leaf extract. The specific goals were to assess the efficacy of lowering blood uric acid and evaluate the acute and semi-chronic toxicity of the extract. Research subjects and methods: The study involved evaluating the uric acid-lowering effect of dried lolot leaf extract using a model inducing acute hyperuricemia by injecting potassium oxonate through the peritoneum in white mice. Additionally, acute toxicity tests were conducted on white mice over a 14-day period, and semi-chronic toxicity tests were performed on rats over 28 days. Results: The dried lolot leaf extract, administered at a dose of 300 mg/kg, demonstrated effectiveness in lowering blood uric acid, showing a reduction rate of 36.3% (p<0,05) compared to the control group. Importantly, the dried lolot leaf extract exhibited no acute toxicity at the tested doses, as evidenced by the absence of fatalities in the test batches, preventing the determination of LD50. Furthermore, in semi-chronic toxicity tests on mice subjected to repeated doses (330 mg/kg/day and 990 mg/kg/day) for 28 days, the extract did not display toxicity across parameters assessing general condition, liver function, kidney function, and hematopoietic function. Conclusion: The dried lolot leaf extract was found to effectively lower uric acid without exhibiting signs of toxicity in the experimental animals.